2004
DOI: 10.1128/jvi.78.13.6864-6874.2004
|View full text |Cite
|
Sign up to set email alerts
|

Nef Proteins from Simian Immunodeficiency Virus-Infected Chimpanzees Interact with p21-Activated Kinase 2 and Modulate Cell Surface Expression of Various Human Receptors

Abstract: The accessory Nef protein allows human immunodeficiency virus type 1 (HIV-1) to persist at high levels and to cause AIDS in infected humans. The function of HIV-1 group M subtype B nef alleles has been extensively studied, and a variety of in vitro activities believed to be important for viral pathogenesis have been established. However, the function of nef alleles derived from naturally simian immunodeficiency virus (SIV)-infected chimpanzees, the original host of HIV-1, or from the HIV-1 N and O groups resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 81 publications
(122 reference statements)
5
61
0
Order By: Relevance
“…The requirement of NL4-3 Nef to precipitate NAK activity in the absence of Cdc42 V12 or an appropriate activating mutation in PAK2 suggested that this Nef allele was unable to stimulate PAK2 activity in the transfected cells. However, since previous studies have reported PAK activation by certain Nef alleles, such as SF2 (1) been recently extensively characterized for their functionality, and all were shown to be able to associate with PAK2 if cotransfected with Cdc42 V12 (15). As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…The requirement of NL4-3 Nef to precipitate NAK activity in the absence of Cdc42 V12 or an appropriate activating mutation in PAK2 suggested that this Nef allele was unable to stimulate PAK2 activity in the transfected cells. However, since previous studies have reported PAK activation by certain Nef alleles, such as SF2 (1) been recently extensively characterized for their functionality, and all were shown to be able to associate with PAK2 if cotransfected with Cdc42 V12 (15). As can be seen from Fig.…”
Section: Resultsmentioning
confidence: 62%
“…pEBB-NL4-3-Nef R71 has been described previously (29). All divergent Nef alleles were cloned into pCG plasmid, and they are described elsewhere (15), except for HIV-2 cbl and SIV SYK51. HIV-2 cbl Nef was amplified from an HIV-2-infected culture obtained through the NIH AIDS Research and Reference Reagent Program.…”
Section: Methodsmentioning
confidence: 99%
“…K144 and the sequence surrounding K144 (FK 144 LVP) are conserved between all HIV-1 and SIVcpz sequences (55). The FKLVP motif we identified is located in a ␤-sheet secondary structure (␤4) that is exposed to the surface (54,78,79).…”
Section: Discussionmentioning
confidence: 99%
“…1 results indicate that K144 is required for Nef-mediated CD4 downregulation (Table I). In this regard, it is worthy of note that K144 as well as the motif K 144 LPV are conserved in all sequenced HIV-1 and SIVcpz Nef strains (55).…”
Section: Substitution Of K144 With Arginine Abolished Nef-mediated CDmentioning
confidence: 99%
“…The Nef-NAK association has also been implicated in increased virion infectivity (56). This interaction of PAK with Nef is a highly conserved feature of primary HIV-1 and SIV Nef alleles (57,58), suggesting that this association is important for Nef functions. Moreover, targeting Nef to the plasma membrane is critical to allow NAK association and its autophosphorylation (59 -61).…”
Section: G2amentioning
confidence: 99%